Tantangan dan Optimalisasi Asesmen Digital dalam Transformasi Pembelajaran: Studi Kasus Di SMPN 10 Kendari - Asmawati Asmawati; Sahidin Sahidin; La Baso; Dwi Wahyuningsih; Lilianti Lilianti (Universitas Kristen Satya Wacana, 2026)
Despite the rapid expansion of digital assessment practices, existing studies largely focus on macro-level implementation or technological effectiveness, with limited attention to how governance, organizational readiness, and user experiences interact within real school contexts, particularly in developing countries. This study examines the implementation of digital assessment in a junior secondary school in Indonesia through a qualitative single-case study approach, highlighting governance dynamics, infrastructure readiness, user experiences, and operational challenges. Data were collected through in-depth interviews, observations, and document analysis involving school leaders, teachers, IT staff, and students, and analyzed using thematic analysis. The findings identify five interconnected themes. The study demonstrates that digital assessment effectiveness emerges not solely from technology adoption but from the interaction between leadership structures, infrastructure conditions, and user adaptation processes. By positioning digital assessment as an organizational and socio-technical practice rather than a purely technological innovation, this case study offers a contextualized theoretical perspective relevant to schools undergoing digital transition. The findings also provide broader insights for education systems in developing contexts, emphasizing that sustainable digital assessment requires governance capacity, equitable access strategies, and adaptive implementation models beyond technological provision alone.